Inflammatory Myofibroblastic Tumor A Rare Case in Kidney (Bangladesh Journal of Urology, 2022)
Inflammatory Myofibroblastic Tumour (IMT) or ‘pseudotumour’ of the kidney is a uncommon benign tumour, common in young adults with unknown etiology. Clinical feature and radiological investigations are usually inconclusive. Often, biopsy is inconclusive required a management similar to that of Renal Cell Cancer (RCC). Diagnosis is based on immunohistochemistry. We are reporting a case of IMT in a 32-year-old female patient who presented with left flank pain and haematuria which on evaluation was suggestive of left renal cell carcinoma. IMT was confermed by Surgery, histopathological examination and Immunohistochemistry.Bangladesh J. Urol. 2021; 24(1): 112-115